Evaluating Traditional and Modern Laboratory Techniques for Determining Permanent Wilting Point - N. Parker; A. Patrignani (Kansas Agricultural Experiment Station Research Reports, 2021)
The permanent wilting point is often considered the lower limit for plant available water and can be measured in the laboratory using a pressure plate apparatus (traditional method) or a dewpoint water potential meter (modern method). However, recent evidence suggests substantial discrepancy between the soil moisture at the permanent wilting points derived from these two laboratory techniques. This preliminary study investigated the magnitude of the discrepancy between permanent wilting points derived from traditional and modern laboratory techniques and the concomitant effects on plant available water estimations. For the analysis, a total of 21 undisturbed soil samples were collected from the top 20 inches of the soil profile at 18 locations of the Kansas Mesonet. The soil moisture content at the permanent wilting point measured using the pressure plate apparatus was 22% higher in clay loam soils and 25% higher in the clay soils than the soil moisture values obtained using a dewpoint water potential meter. When using the pressure plate apparatus, the resulting plant available water capacity (PAWC) was 33% lower in clay loam soils and 57% lower in clay soils compared to the PAWC estimated using the dewpoint water potential meter. Only minor discrepancies of about 8 to 9% were observed in both the resulting permanent wilting point and the estimated PAWC in the silt loam and sandy loam soils.
Keywords: plant available water; traditional method; wilting point; soil water retention curve